Kwahulé et Tarnagda : le théâtre africain entre le stéréotype et l’originalité - Wołowski, Witold; Jakubczuk, Renata (Romanica Silesiana, 2021)
After a short presentation of theatrical definitions of stereotypes, this article offers an hermeneutic study, focused on the elements of stereotypes and strategies of de-stereotyping in two contemporary African plays: Bintou (1997) by Koffi Kwahulé and Les Larmes du ciel d’août -Tears of the August sky (2010) by Aristide Tarnagda. The analysis aims to demonstrate how Koffi Kwahulé et Aristide Tarnagda indulge, possibly unknowingly, in a subtle play with a cliché.